Microtubules in viral replication and transport. (22nd March 2013) - Niehl, Annette; Peña, Eduardo J.; Amari, Khalid; Heinlein, Manfred
Summary Viruses use and subvert host cell mechanisms to support their replication and spread between cells, tissues and organisms. Microtubules and associated motor proteins play important roles in these processes in animal systems, and may also play a role in plants. Although transport processes in plants are mostly actin based, studies, in particular with Tobacco mosaic virus (TMV) and its movement protein (MP), indicate direct or indirect roles of microtubules in the cell‐to‐cell spread of infection. Detailed observations suggest that microtubules participate in the cortical anchorage of viral replication complexes, in guiding their trafficking along the endoplasmic reticulum (ER)/actin network, and also in developing the complexes into virus factories. Microtubules also play a role in the plant‐to‐plant transmission of Cauliflower mosaic virus (CaMV) by assisting in the development of specific virus‐induced inclusions that facilitate viral uptake by aphids. The involvement of microtubules in the formation of virus factories and of other virus‐induced inclusions suggests the existence of aggresomal pathways by which plant cells recruit membranes and proteins into localized macromolecular assemblies. Although studies related to the involvement of microtubules in the interaction of viruses with plants focus on specific virus models, a number of observations with other virus species suggest that microtubules may have a widespread role in viral pathogenesis.